The term structure of equity premia in an affine arbitrage-free model of bond and stock market dynamics - Wolfgang Lemke; Thomas Werner (European Central Bank (ECB), 2009)
We estimate time-varying expected excess returns on the US stock market from 1983 to 2008 using a model that jointly captures the arbitrage-free dynamics of stock returns and nominal bond yields. The model nests the class of affine term structure (of interest rates) models. Stock returns and bond yields as well as risk premia are affine functions of the state variables: the dividend yield, two factors driving the one-period real interest rate and the rate of inflation. The model provides for each month the `term structure of equity premia', i.e. expected excess stock returns over various investment horizons. Model-implied equity premia decrease during the `dot-com' boom period, show an upward correction thereafter, and reach highest levels during the financial turmoil that started with the 2007 subprime crisis. Equity premia for longer-term investment horizons are less volatile than their short-term counterparts.
Keywords: E43; G12; 330; Affine term structure models; asset pricing; Equity premium; Risikoprämie; Zinsstruktur; Kapitaleinkommen; Aktienmarkt; Öffentliche Anleihe; CAPM; USA